Incidence of bleeding after minor oral surgery in patients on dual antiplatelet therapy: a systematic review and meta-analysis. Issue 1 (January 2020) - Ockerman, A.; Bornstein, M.M.; Leung, Y.Y.; Li, S.K.Y.; Politis, C.; Jacobs, R.
Abstract: Bleeding is a feared complication of minor oral surgery in patients on treatment with antiplatelet agents and there is no agreed strategy regarding the cessation or not of antiplatelet treatment. The aim of this systematic review was to evaluate bleeding with minor oral surgery in patients on dual antiplatelet therapy (DAPT), single antiplatelet therapy (SAPT), or no antiplatelet therapy (no APT). The PubMed, Embase, Web of Science, and Cochrane Library databases were screened. Sixteen studies were included. DAPT was continued in all studies. The perioperative bleeding risk was significantly higher for DAPT than for SAPT (risk ratio (RR) 10.16, P  =  0.010; risk difference (RD) 0.35, P  =  0.269), but not higher compared to no APT (RR 6.50, P  =  0.057; RD 0.19, P  =  0.060). The postoperative bleeding risk was significantly elevated for DAPT compared to SAPT (RR 2.61, P  =  0.010) and no APT (RR 3.63, P  =  0.035), but only by 1% (RD 0.01, P  =  0.103) and 1% (RD 0.01, P  =  0.421), respectively. Clinically, this may be considered quite similar. Additionally, local haemostatic measures could control all reported bleeding and no lethal events occurred. Therefore, DAPT interruption is not advised before minor oral surgery.